ECONOMICS - Sloman John (Prentice Hall, 2000)
INTRODUCING ECONOMICS SUPPLY AND DEMAND GOVERMENT INTERVENTION IN THE MARKET BACKGROUND TO SUPPLY PROFIT MAXIMASING ALTERNATIVE THEORIES OF THE FIRM
INTRODUCING ECONOMICS SUPPLY AND DEMAND GOVERMENT INTERVENTION IN THE MARKET BACKGROUND TO SUPPLY PROFIT MAXIMASING ALTERNATIVE THEORIES OF THE FIRM